Leadership and Rewards Drive Performance-Based Budgeting in Indonesia - Sunari, Sunari; Biduri, Sarwenda (Indonesian Journal of Public Policy Review, 2024)
This research investigates the impact of organizational commitment, human resource quality, leadership style, and rewards on performance-based budgeting in Sidoarjo Regency's local government agencies. Using a quantitative approach and surveying 100 employees, data were collected via closed questionnaires and analyzed using SPSS Statistics software version 26. Results show that while organizational commitment has an insignificant impact, leadership style and rewards significantly influence performance-based budgeting, and human resource quality has no effect. These findings highlight the importance of effective leadership and reward systems in enhancing budget implementation. Limitations include a restricted sample size, suggesting further research with broader scope and additional variables. Highlight: Leadership Impact: Leadership style significantly affects performance-based budgeting implementation. Rewards Role: Rewards enhance employees' performance and budget implementation. Human Resources: Quality of human resources does not impact budget implementation. Keywoard: Organizational Commitment, Human Resource Quality, Leadership Style, Rewards, Performance-Based Budgeting